2017
DOI: 10.1111/nep.12860
|View full text |Cite
|
Sign up to set email alerts
|

Replication of genome‐wide association study identified seven susceptibility genes, affirming the effect of rs2856717 on renal function and poor outcome of IgA nephropathy

Abstract: rs2856717 may influence the clinical characteristics and poor outcome of IgAN. Further studies are warranted to explore the mechanisms for such genotype-disease phenotype association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
1
9
0
Order By: Relevance
“…In this study, we determined patients carrying rs2856717-T had an increased risk for disease progression. The result replicated a recent study (21) from southwest China showing associations between rs2856717/TT or TC and increased risk for IgA nephropathy progression. To further dissect the HLA region, we next phased four SNPs (rs7763262, rs9275224, rs2856717, and rs9275596) in the HLA-DQ/DR region and tested their Genetic risk score for each SNP was calculated based on its genotype, i.e.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we determined patients carrying rs2856717-T had an increased risk for disease progression. The result replicated a recent study (21) from southwest China showing associations between rs2856717/TT or TC and increased risk for IgA nephropathy progression. To further dissect the HLA region, we next phased four SNPs (rs7763262, rs9275224, rs2856717, and rs9275596) in the HLA-DQ/DR region and tested their Genetic risk score for each SNP was calculated based on its genotype, i.e.…”
Section: Discussionsupporting
confidence: 87%
“…It is possible that incorporating genetic risk factors such as susceptibility loci identified in GWAS to current risk models could enhance their performance because the multihit pathogenesis model suggests these loci may potentially influence the pathogenesis and severity of IgA nephropathy (3). A post-GWAS revealed that △CFHR3,1 (a deletion variant encompassing CFHR1 and CFHR3) underlining the top signal on chromosome 1 might reduce tubulointerstitial injury (20), and tag single nucleotide polymorphisms (SNPs) in HLA-DQ/DR region might accelerate IgA nephropathy progression (10,21). Further, a genetic risk score including nine susceptibility loci identified in GWAS could predict ESKD in IgA nephropathy (22).…”
Section: Introductionmentioning
confidence: 99%
“…This polymorphism was previously discovered in association with increased susceptibility to immunoglobulin A nephropathy (IgA) in Chinese patients [22] (Figure 4). It was significantly associated with macroscopic hematuria of IgA patients from the Western Chinese Han population [40]; this polymorphism's minor variation had the exact opposite effect on the pathogenesis of IMN and IgAN, indicating a completely different role for this SNP for two types of primary glomerulonephritis [41] (Figure 4). rs9275596 was identified as a Peanut Allergy (PA)-specific locus in a GWAS in participants of European ancestry; the result obtained was confirmed in a replication study of independent samples from the same cohort [42] (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported cases of IgAN and C1q nephropathy associated with TRPC6 mutations (7,22), but there is no further explanation for the deposition of immune complexes in the kidney. It has been reported that several candidate genes relating to IgAN are involved in cytokine pathways, immunoregulation, and glycosylation (23,24). Cox et al identified 23 genes with candidate pathogenic variants functionally related to a large network of immune-related pathways.…”
Section: Discussionmentioning
confidence: 99%